2013
DOI: 10.1249/mss.0b013e3182732b2f
|View full text |Cite
|
Sign up to set email alerts
|

Maximal Aerobic and Anaerobic Exercise Responses in Children with Cerebral Palsy

Abstract: Children with CP have decreased aerobic and anaerobic exercise responses, but decreases in respiratory and aerobic exercise responses were not as severe as predicted by motor impairment. Future research should reveal the role of inactivity on the exercise responses of children with CP and possibilities for improvement through training interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
58
4

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(65 citation statements)
references
References 30 publications
2
58
4
Order By: Relevance
“…increased CR), which is only possible if VO 2max is reasonably high. A recent study from the authors' laboratory [6] in children with CP demonstrated that PPO (-25%) and Wingate PO (-40%) were more depressed than VO 2max (-15%) compared to age matched controls. These data support the concept that limitations in mechanical power production (e.g.…”
Section: Discussionmentioning
confidence: 92%
“…increased CR), which is only possible if VO 2max is reasonably high. A recent study from the authors' laboratory [6] in children with CP demonstrated that PPO (-25%) and Wingate PO (-40%) were more depressed than VO 2max (-15%) compared to age matched controls. These data support the concept that limitations in mechanical power production (e.g.…”
Section: Discussionmentioning
confidence: 92%
“…They have independent mobility when using assistive mobility devices for short distances but may use a wheelchair for community mobility, whereas children classified as GMFCS levels I and II walk independent without using assistive mobility devices (Palisano et al, 1997). Research suggests that children with CP in GMFCS levels I, II, and III tend to have poorer physical fitness than children with no physical disabilities (Hoofdwijk et al, 1995;Verschuren & Takken, 2010;Balemans et al, 2013b), which may lead to a lower health status and higher risk for developing secondary conditions (Fowler et al, 2007). Little is known about the fitness levels of children and youth classified as GMFCS level IV.…”
mentioning
confidence: 99%
“…On the other hand, lower limb rehabilitation generally consists on gross motor activities involving repetitive and coordinated movements with both limbs (walking, cycling, etc. ), what sometimes does not require a conscious effort (Balemans et al, 2013;Bryant et al, 2012;Chen et al, 2012;Damiano, 2006;Leunkeu, Shepard & Ahmaidi, 2012;Mattern-Baxter et al, 2013), resulting in improvements in gait performance and gross motor ability (Baxter et al, 2013;Damiano, 1995;DiBiaso & Lewis, 2013;Johnson et al, 2011;Willoughby, Dodd, Shields & Foley, 2010). However, it is necessary to distinguish between the different types of training (strengthening, aerobic training) in order to provide a clearer picture of how each training modality may benefit people with CP.…”
Section: Discussionmentioning
confidence: 99%
“…This pathology is the most frequent cause of physical disability in children (Balemans et al, 2013;Chen et al, 2012;Reddihough & Collins, 2003), with anPRIEGO QUESADA J.I. ; LUCAS-CUEVAS A.G.; LLANA-BELLOCH S.; PÉREZ-SORIANO P.…”
Section: Introductionmentioning
confidence: 99%